The privatisation of the back wards: the accommodation of people with intellectual disability and people with mental illness in licensed boarding houses in Sydney - Drake, Gabrielle M (Curtin University, 2010)
This thesis explores the use of licensed boarding houses in Inner Sydney as an accommodation option for people with intellectual disability and people with mental illness. Deinstitutionalisation, a significant social policy of the last century was introduced into Australia in the 1960’s and 1970’s, and involved the closure of large institutions and the integration of former residents into the community. One of the community-based accommodation options used for people leaving institutions was boarding houses. This research explores the extent to which boarding houses enact the human rights principles of deinstitutionalisation and contribute to the quality of life of residents with intellectual disability and residents with mental illness.The research draws on an extensive literature review and policy and legislative analysis. Denzin’s interpretive interactionism was used as the overarching methodological framework of the study. Informing the research are forty interviews with a range of participants including current and former licensed boarding house residents, proprietors, and staff of community organisations and government agencies.The results of this research provide evidence that licensed boarding houses are a form of transinstitutionalisation and do not serve to enact the human rights principles articulated in current policy and legislation. This thesis argues for the staged deinstitutionalisation of licensed boarding houses in New South Wales.